Recombinant expression of Aryl Hydrocarbon Receptor for quantitative ligand-binding analysis - Fan, MingQi; Bell, Alex R.; Bell, David Robert; Clode, Sally; Fernandes, Alwyn; Foster, Paul M.D.; Fry, Jeffery R.; Jiang, tao; Loizou, George; MacNicoll, Alan; Rose, Martin; Miller, Brian G.; et al. (Elsevier, 2009)
Recombinant expression of the Aryl Hydrocarbon Receptor (AhR) yields small amounts of ligand- binding competent AhR. Therefore, Spodoptera frugiperda (Sf9) cells and baculovirus have been evaluated for high level and functional expression of AhR. Rat and human AhR were expressed as soluble protein in significant amounts. Expression of ligand-binding competent AhR was sensitive to the protein concentration of Sf9 extract, and co-expression of the chaperone p23 failed to affect the yield of functional ligand-binding AhR. The expression system yielded high levels of functional protein, with the ligand-binding capacity (Bmax) typically 20- fold higher than that obtained with rat liver cytosol. Quantitative estimates of the ligand-binding affinity of human and rat AhR were obtained; the Kd for recombinant rat AhR was indistinguishable from that of native rat AhR, thereby validating the expression system as a faithful model for native AhR. The human AhR bound TCDD with significantly lower affinity than the rat AhR. These findings demonstrate high-level expression of ligand-binding competent AhR, and sufficient AhR for quantitative analysis of ligand-binding.